The high dynamics tracking capability for power descending in Chinese Chang'E-3 mission. Issue 1 (1st July 2017) - Hao, Wanhong; Lu, Mingquan; Li, Zan; Wang, Hong; Fan, Min; Zhu, Zhiyong; Shi, Shanbin; Cheng, Cheng; Han, Songtao; Li, Haitao
Abstract: As the exploration into the lunar and deep space becomes more diverse and profound, the flight process of the spacecraft is quite complex, which highly demands flight status monitoring and precise navigation. Accurate phase recovery in radio telecommunication is essential. This paper demonstrates the high dynamic tracking capability for power descending in Chinese Chang'E-3 mission, using open loop data recoding along with software phase lock loop tracking. Raw data recorded by Chinese Jiamusi and Kashi big antennas, as well as ESA's New Norcia big antenna, have been used to recover the Doppler frequency for almost all the power descending phase. The standard deviation of phase tracking errors is around 5°. The phase tracking results and its variation characteristics are highly correlated with the flight events happening. The high dynamic phase tracking capability demonstrated in this paper have large flexibility and could be applied to flight operations in the future lunar and deep space missions.